As Representações do dia do professor no Jornal A União durante o regime civil militar brasileiro (1964-1985) - Silva, João Batista Barbosa da (2016)
The present study has the objective to understand the Teacher Day building, in Paraíba, using A União journal, during the Brazilian civil military regimen. For making the purposed objective, a documental research about the legislation that ruled the Teacher Day was done, seeking to understand the relations between the October 15th day and First Letters Law of October 15th in 1827, the laws that ruled the National Education no. 4.024 of December 20th in 1961, no. 5.540/1968 and no. 5.692/1971. About the bibliographical research, Vicentini and Lugli (2009) title was emphasized, named História da profissão docente no Brasil: Representações em Disputa, offering subsidies and references to deep the research. An UFPB and UNICAMP data basis survey was done, using the ANPED site, and others academic institutions. It sought to relate all the found documents at the publicized reports, news and notes of A União journal, between 1964 and 1985, being chosen October 13th and 18th of every year to be analyzed. The cited journal choice happened because it was a journal of the Paraíba State Government, principal mouth of the military government.